2018
DOI: 10.1111/jors.12399
|View full text |Cite
|
Sign up to set email alerts
|

Veblen goods and urban distinction: The economic geography of conspicuous consumption

Abstract: A fundamental observation of 21st century cities is that they have become great centers of consumption. In this paper, we seek to understand the geographic variation in consumer behavior. Using Consumer Expenditure Survey (CE), we analyze how consumption differs across 21 major U.S. metropolitan areas, and the association between urban characteristics and consumption. We extend previous geographic analysis of consumption to include luxury goods that are socially visible (conspicuous consumption) and luxury goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…That extrinsic aspiration is driven by external validation suggests its connection to conspicuous consumption, a concept coined by Thorstein Veblen ([1899] 2017) who argued that social status shapes consumption practices (Trigg, 2001). Conspicuous consumption entails ‘the purchase of goods that do not exhibit additional utility or functionality but offer status and reveal socio-economic position’ (Currid-Halkett et al, 2019: 84). Bourdieu (1984: 31) refers to this as a form of ‘naïve exhibitionism (.…”
Section: The Importance Of Lifestyle: Social Class Aspiration and Con...mentioning
confidence: 99%
“…That extrinsic aspiration is driven by external validation suggests its connection to conspicuous consumption, a concept coined by Thorstein Veblen ([1899] 2017) who argued that social status shapes consumption practices (Trigg, 2001). Conspicuous consumption entails ‘the purchase of goods that do not exhibit additional utility or functionality but offer status and reveal socio-economic position’ (Currid-Halkett et al, 2019: 84). Bourdieu (1984: 31) refers to this as a form of ‘naïve exhibitionism (.…”
Section: The Importance Of Lifestyle: Social Class Aspiration and Con...mentioning
confidence: 99%
“…Focusing on the effect of urbanization on consumption expenditures, Currid-Halkett et al (2017) demonstrated that people living in metropolitan areas are more willing to spend on conspicuous consumptions (i.e., goods showing social status and wealth) stimulated by higher income, the desire to reveal status and by a greater product availability (Glaeser, 2011). Nevertheless, Handbury and Weinstein (2015) found that luxury goods are cheaper in urban areas, suggesting economies of scale for wealthy individuals, while rural residents may hold different attitudes toward how to spend their money wisely (Zhu et al, 2021).…”
Section: Urbanization Swb and Consumption Expenditurementioning
confidence: 99%
“…In line with the Global Council for Happiness and Wellbeing (2019), although strong evidence on a positive relationship between happiness and degree of urbanization still persists, the idea that increasing the level of urbanization of a specific country or region could be associated with an improvement in subjective wellbeing is not always found empirically (Morrison, 2021). Beside the influence of urbanization on SWB, the urban environment in which individuals live may contribute also to shape heterogenous consumption patterns, closely related to the socio-economic and industrial mix of cities (Currid-Halkett et al, 2017). Moreover, empirical evidence suggests likely different reactions to specific expenditure categories across urbanized areas (Handbury & Weinstein, 2015).…”
mentioning
confidence: 99%
“…Simply put, individuals buy the most important goods and services of their necessities based on their needs and ability to pay. (Currid-Halkett et al 2019) classified consumption into three frameworks from an economic geography perspective, 1. commodification of cultures 2. highend luxurious 3. amenities. In this research, we investigate the potential usage of OSM data to map the spatial dimension of these main categories of consumption in the city.…”
Section: Introductionmentioning
confidence: 99%
“…The first one represents cultural centres such as cinemas and theatres. The second one can be viewed as conspicuous goods (Veblen or luxury goods), and the last one as necessary goods for life (Currid-Halkett et al 2019).…”
Section: Introductionmentioning
confidence: 99%